Multi-Level Interactions between the Nuclear Receptor TRα1 and the WNT Effectors β-Catenin/Tcf4 in the Intestinal Epithelium - Sirakov, Maria; Skah, Seham; Lone, Imtiaz Nisar; Nadjar, Julien; Angelov, Dimitar; Plateroti, Michelina (PLOS ONE, 2012)
Intestinal homeostasis results from complex cross-regulation of signaling pathways; their alteration induces intestinal tumorigenesis. Previously, we found that the thyroid hormone nuclear receptor TRα1 activates and synergizes with the WNT pathway, inducing crypt cell proliferation and promoting tumorigenesis. Here, we investigated the mechanisms and implications of the cross-regulation between these two pathways in gut tumorigenesis in vivo and in vitro. We analyzed TRα1 and WNT target gene expression in healthy mucosae and tumors from mice overexpressing TRα1 in the intestinal epithelium in a WNT-activated genetic background (vil-TRα1/Apc mice). Interestingly, increased levels of β-catenin/Tcf4 complex in tumors from vil-TRα1/Apc mice blocked TRα1 transcriptional activity. This observation was confirmed in Caco2 cells, in which TRα1 functionality on a luciferase reporter-assay was reduced by the overexpression of β-catenin/Tcf4. Moreover, TRα1 physically interacted with β-catenin/Tcf4 in the nuclei of these cells. Using molecular approaches, we demonstrated that the binding of TRα1 to its DNA target sequences within the tumors was impaired, while it was newly recruited to WNT target genes. In conclusion, our observations strongly suggest that increased β-catenin/Tcf4 levels i) correlated with reduced TRα1 transcriptional activity on its target genes and, ii) were likely responsible for the shift of TRα1 binding on WNT targets. Together, these data suggest a novel mechanism for the tumor-promoting activity of the TRα1 nuclear receptor.